MOTIVATIONS OF RELIGIOUS CONCEPTS AND IDEAS IN NOMINATION OF ORОOBJECTS OF SOUTH UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
When nominating the oroobjects the religious beliefs, concept, objects and phenomena considered sacred, divine and exhibit a peculiar motivational feature. The article discusses similar phenomena in the examples of the oronims of Southern Uzbekistan.